2018
DOI: 10.1016/j.rboe.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of core decompression in the early stages of osteonecrosis of the femoral head? Evaluation of the surgical result by functional score and radiological follow-up

Abstract: ObjectivesThis study is aimed at evaluating whether core decompression of the femoral head in the early stages of femoral head osteonecrosis improves patients’ subjective perception of pain and avoids the progression of the disease to a femoral head collapse and a final indication of total hip arthroplasty.MethodsEighteen patients (30 hips) in the early stages of the disease (Ficat and Arlet 1 and 2A) were evaluated through clinical, radiological, risk factor maintenance, and by the functional Merle D’Aubigné,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
9
0
5
Order By: Relevance
“…Majority of the studies, 20 (40%), used the original “Ficat” classification [ 24 , 27 , 29 , 32 , 34 , 36 , 41 , 46 , 48 52 , 56 59 , 61 , 62 , 67 ]. Ten studies (20%) followed the “Modified Ficat” classification [ 12 , 25 , 31 , 44 , 47 , 54 , 55 , 63 , 65 , 70 ] and other eleven (22%) [ 26 , 28 , 30 , 37 39 , 45 , 60 , 66 , 68 , 69 ] used the ARCO system. Finally, nine studies (18%) [ 12 , 13 , 33 , 35 , 40 , 42 , 43 , 53 , 64 ] applied the “Steinberg/University of Pennsylvania” classification.…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the studies, 20 (40%), used the original “Ficat” classification [ 24 , 27 , 29 , 32 , 34 , 36 , 41 , 46 , 48 52 , 56 59 , 61 , 62 , 67 ]. Ten studies (20%) followed the “Modified Ficat” classification [ 12 , 25 , 31 , 44 , 47 , 54 , 55 , 63 , 65 , 70 ] and other eleven (22%) [ 26 , 28 , 30 , 37 39 , 45 , 60 , 66 , 68 , 69 ] used the ARCO system. Finally, nine studies (18%) [ 12 , 13 , 33 , 35 , 40 , 42 , 43 , 53 , 64 ] applied the “Steinberg/University of Pennsylvania” classification.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless the clinical outcomes have varied widely [39] . However, other studies reported [40][41][42][43] that core decompression combined with adjuvant therapy can improve the symptoms of pain, but it did not affect the progress and collapse of femoral head, especially in the late stage of ONFH. So, there is still controversial about core decompression (with or without adjuvant therapy) for ONFH.…”
Section: Discussionmentioning
confidence: 92%
“…Nos estudos analisados foi possível verificar a grande prevalência de adultos entre a terceira e quinta década de vida, associado a fatores etiológicos promotores da reabsorção óssea como por exemplo, álcool, sequelas de traumas, coagulopatias, lúpus eritematoso sistêmicos, HIV e paciente transplantados em fase de utilização de imunossupressores. 6 Ainda se conhece pouco sobre a fisiopatologia envolvida. Contudo, pode-se verificar que nesta enfermidade ocorre a interrupção do fluxo sanguíneo para a cabeça do fêmur, acarretando infarto ósseo.…”
Section: Discussionunclassified
“…2021 porção cabeça femoral torna-se uma região vulnerável a danos e deformações antes mesmo que o processo de remodelação seja iniciado. 6 Através das buscas na literatura observou-se que a bilateralidade foi considerada como fator prognóstico por alguns autores, havendo, portanto, divergência dentro desta temática. A bilateralidade da necrose foi encontrada em 39 dos 77 pacientes portadores de osteonecrose avaliado no estudo, o que correspondeu a 50,6%.…”
Section: Discussionunclassified
See 1 more Smart Citation